Investigation on MoS2(1-x)Te2x Mixture Alloy Fabricated by Co-sputtering Deposition. (31st January 2017) - Hibino, Y.; Ishihara, S.; Sawamoto, N.; Ohashi, T.; Matsuura, K.; Machida, H.; Ishikawa, M.; Sudo, H.; Wakabayashi, H.; Ogura, A.
ABSTRACT: We report the synthesis of MoS2(1-x) Te2x by co-sputtering deposition and effect of mixture on its bandgap. The deposition was carried out at room temperature, and the sputtering power on individual MoS2 and MoTe2 targets were varied to obtain films with different compositions. Investigation with X-ray photoelectron spectroscopy confirmed the formation of Mo-Te and Mo-S bonds after post-deposition annealing (PDA), and one of the samples exhibited composition ratio of Mo:S:Te = 1:1.2:0.8 and 1:1.9:0.1 achieving 1:2 ratio of metal to chalcogen. Bandgap of MoS1.2 Te0.8 and MoS1.9 Te0.1 was evaluated with Tauc plot analysis from the extinction coefficient obtained by spectroscopic ellipsometry measurements. The obtained bandgaps were 1.0 eV and 1.3 eV. The resulting bandgap was lower than that of bulk MoS2 and higher than that of bulk MoTe2 suggesting mixture of both materials was achieved by co-sputtering.